2019
DOI: 10.1177/0844562118819924
|View full text |Cite
|
Sign up to set email alerts
|

“I Didn’t Need People’s Negative Thoughts”: Women With Intellectual and Developmental Disabilities Reporting Attitudes Toward Their Pregnancy

Abstract: Background Since the illegalization of involuntary sterilization of persons with intellectual and developmental disabilities, there has been an increase in childbearing in this population. However, women with intellectual and developmental disabilities continue to experience prejudicial attitudes toward their pregnancies. Objective To analyze the experiences of women with intellectual and developmental disabilities regarding their perceptions of support persons’ attitudes toward their pregnancies. Methods Thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…The need for support in these situations is rarely met and often not adapted to mothers’ cognitive abilities (Janeslätt et al., 2019). Pregnant women with ID prefer support from caregivers perceived as non‐judgemental and tend to avoid contact with persons perceived as a threat, such as authorities (Potvin, Barnett, Brown, & Cobigo, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The need for support in these situations is rarely met and often not adapted to mothers’ cognitive abilities (Janeslätt et al., 2019). Pregnant women with ID prefer support from caregivers perceived as non‐judgemental and tend to avoid contact with persons perceived as a threat, such as authorities (Potvin, Barnett, Brown, & Cobigo, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Several items had changes that were nearly significant, strengthening the evidence that discussing the themes in the Parenting Toolkit Third, a tendency was found that the participants moved from extreme to less extreme values (e.g., from 'strong yes' to 'yes'). This may be thanks to the way in which the Parenting Toolkit was presented: non-judgementally, as recommended by Potvin et al (2019), and adapted to the target group, as described by Azar et al (2013).…”
Section: Discussionmentioning
confidence: 99%
“…Third, a tendency was found that the participants moved from extreme to less extreme values (e.g., from ‘strong yes’ to ‘yes’). This may be thanks to the way in which the Parenting Toolkit was presented: non‐judgementally, as recommended by Potvin et al (2019), and adapted to the target group, as described by Azar et al (2013). This was the intention when the Parenting Toolkit was first created.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, adequate social support and supported decision-making should be provided for the reproductive rights of WIDs. 34 If circumstances make them unfit for childbearing, the PFPL should support scientific and reasonable contraceptive and birth control measures rather than prohibiting WIDs from marrying. Second, the PFPL should explicitly include WIDs as part of the subject of reproductive rights.…”
Section: Discussionmentioning
confidence: 99%